Desempenho de meios filtrantes na filtração de gases a altas pressões - Tanabe, Eduardo Hiromitsu (2011)
The presence of residue in the transport of natural gas in pipelines may result in numerous losses for the gas companies, such as obstruction of measuring equipment, decrease in product quality, and reduction in the lifetime of equipment. A very efficient and inexpensive way for removal of particles is the use of gas filtration. Despite the wide applicability of filters, there are very few studies on natural gas filtration, due to their operating conditions, because they work at high pressures. Thus, research in this area is extremely important to obtain more information about this subject. Therefore, this study aimed to examine the behavior of different filter media used in gas filtration at high pressures. The particulate matter used was the phosphate concentrate and the filter media were polyester, polypropylene, cellulose and metal. The absolute pressure of the system varied from 93 kPa to 693 kPa and the volumetric flow from 14 l/min to 74 l/min in the permeability trials and the fluid used was compressed air. The system pressures of 193, 393 and 693 kPa were used in the filtration trials and the superficial gas velocity was kept constant at 0.05 m/s. The results showed that the permeability constants, k1 and k2, did not present significant variations with the increase in the system pressure, that is, the values tended to a constant value. Simulations to determine pressure drop using natural gas as fluid were performed considering that the permeability constants did not present large variations. The results indicated that the increase in system pressure resulted in greater filtering capacities for a given pressure drop. It was observed that the highest absolute pressure applied to the system (693 kPa) provided the lowest pressure drop at the filter for the same powder mass collected in the filtration trials. An analysis of the dust cakes porosity revealed that the increase in pressure resulted in more porous cakes which were less resistant to gas flow. Also, it was verified that the increase in the system pressure provided an increase in the fractional efficiency of the filters for particles smaller than 5 μm.